Activation of mTORC1 in two steps: Rheb-GTP activation of catalytic function and increased binding of substrates to raptor1. (20th January 2009) - Avruch, Joseph; Long, Xiaomeng; Lin, Yenshou; Ortiz-Vega, Sara; Rapley, Joseph; Papageorgiou, Angela; Oshiro, Noriko; Kikkawa, Ushio
Abstract : The signalling function of mTOR complex 1 is activated by Rheb-GTP, which controls the catalytic competence of the mTOR (mammalian target of rapamycin) kinase domain by an incompletely understood mechanism. Rheb can bind directly to the mTOR kinase domain, and association with inactive nucleotide-deficient Rheb mutants traps mTOR in a catalytically inactive state. Nevertheless, Rheb-GTP targets other than mTOR, such as FKBP38 (FK506-binding protein 38) and/or PLD1 (phospholipase D1 ), may also contribute to mTOR activation. Once activated, the mTOR catalytic domain phosphorylates substrates only when they are bound to raptor (regulatory associated protein of mTOR), a separate polypeptide within the complex. The mechanism of insulin/nutrient stimulation of mTOR complex 1 signalling, in addition to Rheb-GTP activation of the mTOR catalytic function, also involves a stable modification of the configuration of mTORC1 (mTOR complex 1) that increases access of substrates to their binding site on the raptor polypeptide. The mechanism underlying this second step in the activation of mTORC1 is unknown.